Learning english abroad : [Unitate didaktikoa - DBH] / Berritzegune Nagusia
While on holiday, many students choose to travel to an English-speakingcountry to improve their level of English. To learn English in countries such asEngland, Ireland or Malta is an unforgettable experience! Students find peersfrom all over the world, who not only go to these countries to learn English, butto seek a fantastic cultural experience.